PENGENDALIAN KECEPATAN MOTOR BRUSHLESS DC (BLDC) MENGGUNAKAN METODE LOGIKA FUZZY - Agung Dwi Yulianta; Sasongko Pramono Hadi; Suharyanto - (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
BLDC motors were operated in many industrial environments, especially flammable industry. Besides, it possessed higher efficiency than induction motors, and smaller dimensions than a conventional direct current motors. Moreover, the absence of brush allowed its treatment became easy and showed almost no noise.Fuzzy logic was used as one of the motor speed controlling methods. The design of fuzzy controllers was done by simulating the output speed based on fuzzy controlling reference in order to obtain optimal control results. Several types of defuzzification used were COA / centroid, bisector, MOM, LOM, and SOM. Transient and calculation methods were used to analyze the ISE design optimization of control. The result showed that defuzzification method was able to follow the speed setting that was provided by COA method.The testing on changes of the speed setting from 1000 rpm to 2000 rpm showed the response characteristics of conventional PID control system with an average value of the rise time (tr) 0.29 second, steady time (ts) 0.9 second, overshoot 8.63%, and the percentage of ISE 98.19%. While results generated on fuzzy control system were average value of rise time (tr) 0.25 second, steady time (ts) 0.27 second, overshoot 0.15% and the percentage of ISE 99.36%. The fuzzy control system which was implemented to set the BLDC motor could improve the performance of conventional PID.